Sucker-Rod Pumping Handbook : Production Engineering Fundamentals and Long-Stroke Rod Pumping - Takacs, Gabor (Waltham, MA : Gulf Professional Publishing, 2015)
Sucker-Rod Pumping Handbook presents the latest information on the most common form of production enhancement in today's oil industry, making up roughly two-thirds of the producing oilwell operations in the world. The book begins with an introduction to the main features of sucker rod pumping and an explanation and comparison of lift methods. It goes on to provide the technical and practical knowledge needed to introduce the new and practicing production engineer and operator to the equipment, technology, and applications required to maintain optimum operating conditions. Sucker-Rod Pumping Handbook is a must-have manual that ensures operators understand the design, components, and operation of sucker rod pump systems, learn the functions of the systems, apply the fundamental production engineering theories and calculations, and accomplish maximum system efficiency by avoiding the typical pitfalls that lead to fatigue and failure.
APPENDIX C -- API GEOMETRY DIMENSIONS OF AIR BALANCED PUMPING UNITSAPPENDIX D -- API GEOMETRY DIMENSIONS OF MARK II PUMPING UNITS; APPENDIX E -- API GEOMETRY DIMENSIONS OF REVERSE MARK PUMPING UNITS; Index
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Sucker rods -- Handbooks, manuals, etc; Oil well pumps; Oil well drilling rigs; TECHNOLOGY & ENGINEERING / Mining; Oil industry; Sucker rods -- Handbooks, manuals, etc; Sucker rods; Oil well drilling rigs; Oil well pumps; Sucker rods; Electronic books; Electronic books; Handbooks and manuals